Stability of the financial system : illusion or feasible concept? - Dombret, Andreas R.; Lucius, Otto (2013)
Since 2008, financial stability has moved to the centre of the policy stage. This volume, combining contributions from leading policy makers and academics, is an essential introduction to the issues.
Includes bibliographical references and index.
oif 15/06/15, ijb 07/03/2019
Loan
Keywords: Economic stabilization; Finance; Monetary policy; Economics